Thesmophoriazusae - Aristophanes,Austin, Colin,Olson, S. Douglas (Oxford University Press, 2018)
Greek text with commentary of Thesmophoriazusae (Women celebrating the Thesmophoria) by Aristophanes.
10.1093/actrade/9780199265275.book.1
Keywords: Kommentar; Euripides; Drama; Demeter; (Greek deity); Cult; Drama; Thesmophoria; Drama; Women; Greece; Drama; Fasts and feasts; Greek religion; Drama